Strengthening Cadre Capacities in Combating Stunting: The "ERKADUTA" Initiative - Sutinbuk, Dedek; Nugraheni, Sri Achadi; Rahfiludin, M. Zen; Setyaningsih, Yuliani (International Journal of Membrane Science and Technology, 2023)
Stunting represents a persistent nutritional challenge arising from prolonged insufficient dietary intake. Especially in the Indonesian context, there is a pressing demand for community empowerment to address stunting in children below the age of two, owing to the multifaceted nature of this problem. In the present research, we executed an intervention by providing support to mothers of toddlers through the establishment of the ERKADUTA center, which served as a collaborative learning space for mothers of toddlers and trained neighborhood leaders (RT activists). The preliminary phase of this research employed a quantitative analytical approach, involving a sample of 96 participants. The examined variables encompassed the Erkaduta Model, the knowledge of mothers with children under the age of two, the attitudes of these children, and the practices of mothers regarding stunting prevention. The analysis incorporated a comparative evaluation before and after the ERKADUTA mentoring intervention, employing the Mann-Whitney test. Subsequently, the influence of these factors was examined using partial least squares. The majority of mothers with toddlers exhibit favorable attitudes toward stunting prevention. The ERKADUTA model plays a significant role in enhancing the knowledge, attitudes, and practices of mothers with children under the age of two. Subsequent analysis revealed that the "practice" variable demonstrated the highest outer loading value of 0.856 and a t-statistic of 21.668, signifying that the ERKADUTA model has the most substantial impact on modifying the practices of mothers with children under the age of five. The ERKADUTA model substantially enhances stunting prevention practices, particularly among mothers with toddlers.